Hate Speech in Myanmar (Journal of Advanced Research in Social Sciences, 2020)
Freedom of expression can be abused in concerning with race, religion or nation, politics and gender and it transfers into a hate speech. This research intends to investigate the gap between the legal ideals and actual practice, especially to understand effectiveness or impact of a draft for the Protection against and Prevention of Hate Speech Law in Myanmar. This paper analyzes the Domestic Laws such as the Constitution of the Republic of the Union of Myanmar, 2008 and the Penal Code, 1861 and the International Covenant on Civil and Political Rights (ICCPR), the International Convention on the Elimination of all forms of Racial Discrimination (ICERD), the Convention on the Elimination of All Forms of Discriminations against Women (CEDAW) and the Genocide Convention relating to international Conventions and international other documents. This research uses a qualitative approach research method, applying analysis of laws. The draft law is required to balance the right to freedom of expression and the prohibition of hate speech. International human rights laws and standards recognize all protected characteristics of human rights that should be comprised all protecting range of any actions to define “hate speech” in the draft law and should not be restricted to ethnicity, religion, nation, politic and gender. The Government should provide the upcoming Law Protection against and Prevention of Hate Speech in Myanmar urgently.